The State and Human Rights NGOs In Cameroon: A Critical Overview of The Relationship (Texas Journal of Philology, Culture and History, 2021)
In Cameroon, there is a vibrant civil society which makes clear the idea that organisations in this sector have important roles to play in the society. This can be attributed to the fact that there are legislations such as the law on freedom of association which allows for the simple creation of associations in the country. Also, there is a good sense of collaboration between the government and the civil society which is a precursor to the fact that the State is aware of the benefits of such collaboration. There is failing obligation of the government to fully promote and protect human rights, as the State is the primary body to promote and protect human rights. Also, despite the move towards cooperation, the State has maintained a stronghold on the civil society with legislations which gives public authorities leverage over human rights defenders, especially. This paper embarks on an analysis of the working relationship between the various State institutions and human rights civil society organisations. As a result, we look at the cooperation and the areas for improvement